THE EFFECT OF TEMPE FLOUR SUBSTITUTION AND THE ADDITION OF COFFEE GROUNDS ON PROTEIN, FIBER, CARBOHYDRATE CONTENT, AND ORGANOLEPTIC QUALITY OF DAHLIA COOKIES - Elizabeth Angela Sitijo; Bambang Sigit Sucahyo; Yuyun Yuniati; Rachma Nur Devianti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Dahlia cookies are a food product generally made using wheat flour as the main ingredient and sugar as a flavor enhancer. Tempeh flour can be used as a substitute for wheat flour because it has a higher protein content, as well as containing essential amino acids and dietary fiber. Coffee grounds are coffee processing waste that still contains bioactive compounds and fiber so it has the potential to be used as an additional ingredient that can contribute to aroma and sensory characteristics. This study aims to determine the effect of tempeh flour substitution and the addition of coffee grounds on the protein, fiber, carbohydrate content, and organoleptic quality of dahlia cookies. This study used an experimental method with a factorial Completely Randomized Design (CRD), consisting of two factors: tempeh flour substitution (30%, 70%, 30%, 70%) and the addition of coffee grounds (6%, 6%, 12%, 12%). The parameters tested included protein content, fiber content, carbohydrate content, and organoleptic tests (color, aroma, taste, and texture). The data from the proximate content analysis were analyzed using ANOVA, while the organoleptic data were analyzed using the Kruskal-Wallis test.